Insects identification in maize crop using WSN - Srinivas, M.; Durgaprasadarao, P. (International Journal of Engineering and Technology, 2019)
In India, every year a large scale of agricultural crops are destroyed by these soil-dwelling pests and White Grubs have most significant damage among them. White Grubs are the larvae of scarab beetle that feeds on the rootlets of the plants. It is considered as the national importance pest of India. Several technologies are being adapted from the past few years in order to control White Grubs. Apparently, they serve as either slow methods or costly. A different framework is developed to sort out the problems faced by the earlier technologies. The use of Smart Greenhouse technology has aided in finding the location of grubs’ larvae efficiently. The capability of EPNs nematode to locate White Grubs is taken as the fundamental methodology to develop a system for tracing the location of White Grubs.The proposed method is mainly invented to find the second instar and third instar of grubs as they are the most damaging stages in the grub lifecycle. MQ-135 is used in the developed hardware to detect the CO2 bursts emerged from the grubs.